2003
DOI: 10.1177/1534735403256419
|View full text |Cite
|
Sign up to set email alerts
|

Immune System Effects of Echinacea, Ginseng, and Astragalus: A Review

Abstract: Traditional herbal medicine provides several remedies for strengthening the body's resistance to illness through effects on immune system components. This review article examines 3 popular herbal immune stimulants that are often of interest to cancer patients. Echinacea, a native of North America, is widely used to prevent, or provide early treatment for, colds. Preclinical studies lend biological plausibility to the idea that echinacea works through immune mechanisms. Numerous clinical trials have been carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
176
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(185 citation statements)
references
References 141 publications
2
176
0
7
Order By: Relevance
“…Some studies have demonstrated activation of an immune response following treatment with echinacea extracts [19], but it is not clear how this might influence the pathogenesis of individuals infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated activation of an immune response following treatment with echinacea extracts [19], but it is not clear how this might influence the pathogenesis of individuals infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Well-known biochemical and pharmacological effects include anti -aging, anti-diabetic, anti-fatigue, along with promoting the synthesis of DNA, RNA and proteins (Attele et al, 2002;Xie, Mehendale, and Yuan 2005;Christensen 2008;King and Murphy 2010). Studies have also shown that ginseng has beneficial effects on the central nervous system, cardiovascular system, and immune system (Block and Mead, 2003; Cancer prevention and inhibition of tumor growth are among other effects (Shin et al, 2000;Shibata 2001;Wang et al, 2007;King and Murphy, 2010). The herb is used as ginseng tea, extract, or raw directly from powdered root (Bucci 2000).…”
Section: About Ginsengmentioning
confidence: 99%
“…Clinically, the hepatoprotective and antioxidant actions of Schizandrae have proven beneficial in the treatment of chronic viral hepatitis 181 . More data are required to determine the clinical effects of Chinese herbs on immunity and to prevent cancer progression 182 .…”
Section: Prevention Of Cancer Progressionmentioning
confidence: 99%